2012
DOI: 10.2174/138161212802481291
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α/Cycloheximide-Induced Oxidative Stress and Apoptosis in Murine Intestinal Epithelial MODE-K Cells

Abstract: In the mouse postoperative ileus model, we have shown an increase in oxidative stress after intestinal manipulation occurring earlier in the mucosa than in the muscular layer, which might contribute to epithelial barrier dysfunction. To address these findings in vitro, we assessed TNF-α/cycloheximide (CHX)-induced oxidative stress and apoptosis in a mouse intestinal epithelial cell line, MODE-K. The influence of heme oxygenase (HO)-1-related products and agents known to reduce reactive oxygen species (ROS) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…We previously found that CORM-A1 and resveratrol reduce both these effects (Babu et al, 2012). We have also recently identified that NOX and mitochondrial ETC complexes (I and II) are the major sources of ROS production during TNF-α/CHX-induced apoptosis (Babu et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We previously found that CORM-A1 and resveratrol reduce both these effects (Babu et al, 2012). We have also recently identified that NOX and mitochondrial ETC complexes (I and II) are the major sources of ROS production during TNF-α/CHX-induced apoptosis (Babu et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…We previously showed that CORM-A1 as well as resveratrol reduced both TNF-α/CHX-induced ROS production and apoptosis in MODE-K IECs (Babu et al, 2012). The aim of the present study was therefore to investigate the influence of CORM-A1 and resveratrol on the different sources of TNF-α/CHX-induced ROS production in MODE-K cells.…”
Section: Or By Oral Infection Withmentioning
confidence: 90%
See 3 more Smart Citations